2022
DOI: 10.1111/clr.13951
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of digital implant impressions in clinical studies: A systematic review

Abstract: Currently, implant-supported prosthodontic restorations are a commonly accepted treatment option for functional and aesthetic rehabilitation of partially and completely edentulous patients (Pjetursson et al., 2012;Srinivasan et al., 2017). In this context, the use of intraoral scanners (IOSs) for digital implant impressions is continuously increasing (Blatz & Conejo, 2019;Michelinakis et al., 2021).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 85 publications
0
36
0
Order By: Relevance
“…The best fit alignment method is used to evaluate the accuracy of different digital impressions by scanning either closed or open tray stone cast using a desktop scanner to fabricate a digital model, which was the best fit aligned over the digital models obtained from scanning intraorally using IOS. It was reported that the best-fit alignment method is suitable for the evaluation of accuracy in one quadrant [ 3 , 31 , 32 ]. This algorithm minimizes the global distances between the test and reference data, and the deviation between the data is measured using the root-mean-square error [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The best fit alignment method is used to evaluate the accuracy of different digital impressions by scanning either closed or open tray stone cast using a desktop scanner to fabricate a digital model, which was the best fit aligned over the digital models obtained from scanning intraorally using IOS. It was reported that the best-fit alignment method is suitable for the evaluation of accuracy in one quadrant [ 3 , 31 , 32 ]. This algorithm minimizes the global distances between the test and reference data, and the deviation between the data is measured using the root-mean-square error [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…This means that the dimensions of the reference model are obtained by using the most accurate methods available today such as coordinate measurement machine (CMM) or an industrial scanner. On the other hand, in clinical conditions, the ground truth or the real dimensions of the patient's intraoral tissues being digitized are not known, and the reference model is obtained by using conventional techniques such as diagnostic stone casts 16–36 …”
Section: Introductionmentioning
confidence: 99%
“…Complete digital workflows for fabricating tooth‐ and implant‐supported crowns and short span fixed dental prostheses obtain similar marginal and internal discrepancies compared with conventional methods 21–35 . The challenge today remains to incorporate IOSs into complete digital workflows for fabricating complete dentures 29 and Kennedy Class I and II removable partial dentures 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several decades, DITs using intraoral scanners have been considered an advantageous alternative to CITs because they improve comfort and are more efficient [8,9]. However, the accuracy of DITs remains inconclusive, and a wide range of values (5.38-810 µm) is documented [10].Most recent studies regarding the accuracy of implant impression techniques are limited to laboratory study designs [11][12][13][14][15][16][17], and only a few clinical studies have been reported [18]. As defined by ISO 5725-1, accuracy comprises trueness and precision.…”
mentioning
confidence: 99%
“…Most recent studies regarding the accuracy of implant impression techniques are limited to laboratory study designs [11][12][13][14][15][16][17], and only a few clinical studies have been reported [18]. As defined by ISO 5725-1, accuracy comprises trueness and precision.…”
mentioning
confidence: 99%